MONITORING THE HEALTH OF DRYLAND ECOSYSTEM ACROSS NORTH-WESTERN NIGERIA USING MULTI-TEMPORAL MODIS-NDVI REMOTE SENSING DATA - Abubakar, M. J.; Mokhtar, J.; Lam, K. C. (FUDMA JOURNAL OF SCIENCES, 2023)
The study aimed at monitoring the health of the dryland ecosystem of Northwestern Nigeria using geospatial techniques. The need for constant monitoring of the ecosystem in order to keep track of its condition viz a viz its ability to produce qualitative and adequate good and service necessary for human survival and economic development cannot be over emphasized. This is particularly so with fragile dryland ecosystem of Northwestern Nigeria due to the constant disturbances it suffers from both natural and anthropogenic drivers, which could negatively affect the structure and functions of the ecosystem. In this study,MODIS – NDVI remote sensing data was used to monitor the health of the dryland ecosystem of North-western Nigeria. Findings of the study indicate a steady decline in the ecosystem health as indicated by the declining trend of mean NDVI values from 0.56 in 2000 to 0.47 in 2016, which is positively correlated (r = 0.85) with the annual rainfall distributions of the area during the same years. Similarly, the spatial extent of the vegetation cover declined from 97% in 2000 to 84% in 2015. This has a very serious implications on the livelihood of the inhabitants of the area as it negatively affects the supply of ecosystem goods and services, threatening the livelihoods in multiple ways. Collaborations amongst different stake holders, sustainable land management practices, environmental protection policies, as well as Ecosystem-based Adaptation (EbA) are recommended as means of addressing this negative development.